Studi Sistem Dispersi Padat Ibuprofen – Manitol Dengan Metode Pelarutan - Rina Wahyuni; Salman Umar; Zulfareda Putri (STIFARM Padang, 2016)
Study of solid dispersions of ibuprofen-manitol by solvent method had been researched. Solid dispersions made in 4 ratio formula, F1; F2; F3 and F4 with ibuprofen-manitol ratio 3: 1, 2: 2, 1: 3, and 0.5: 3.5. Evaluation of solid dispersions of Ibuprofen - Manitol include x-ray diffraction (XRD), FT-IR spectroscopy, scanning electron microscopy (SEM), assay and dissolution test. Results of X-ray diffraction solid dispersion system showed a decrease in intensity of the degree of crystalline ibuprofen. SEM characterization results indicated ibuprofen morphological changes towards more amorphous.